Legacy effects of historical woodland changes on contemporary plant functional composition - Ji-Zhong Wan; Chun-Jing Wang (Forest Ecosystems, 2023)
Considering the legacy of plant functional composition can help assess ecosystem functions and ecosystem services across different spatial scales under land cover changes. Woody plants likely respond to natural and anthropogenic perturbations due to historical events (e.g., agricultural development), thus contemporary plant functional composition may be explained by historical woodland change, a type of land cover change. We propose that historical woodland changes may have legacy effects on contemporary plant functional composition. Here, we used partial least squares regression and linear mixed model analyses to test this assumption by coupling data on community weighted means (CWM) and community weighted variance (CWV) of vegetation plots and calculating the time of woodland existence across different periods from AD 0 to 2017. We found that the legacy effects of historical land cover changes on CWM and CWV during the existence time of woodland, particularly from AD 0 to 900, were drivers of contemporary plant functional composition at large spatial scales. Furthermore, historical woodland changes can affect contemporary plant functional composition, depending on the biome type. Particularly, the CWM of plant height, seed mass, and seed length showed the strongest correlations with woodland changes from AD 1910 to 2010 in tropics with year-round rain, and the CWM of leaf traits correlated with woodland changes from AD 0 to 1700 in tropics with summer rain. Our study provides the effective evidence on the legacy of historical woodland changes and the effects on contemporary plant functional composition, which is crucial with respect to effective management of plant diversity and assessing ecosystem functions and services from local to global scales over time.